First record of Bagauda aelleni (Hemiptera: Reduviidae) from India and notes on its natural history in Sri Lanka - Ranasinghe, Tharindu; Sankararaman, H.; Agarwal, Anubhav; Sumanapala, Amila; Ghate, Hemant (Zootaxa, 2024)
Bagauda aelleni Villiers, 1970 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Leistarchini), described from Sri Lanka, is reported from India for the first time. Based on specimens collected at Sirumalai, Tamil Nadu, the species is redescribed and various aspects of its morphology and life history are highlighted and illustrated.